ANALISIS FAKTOR INTERNAL DAN EKSTERNAL YANG MEMPENGARUHI PERSEPSI MAHASISWA AKUNTANSI TERHADAP TINDAKAN PLAGIARISME DENGAN TEKANAN SEBAGAI VARIABEL MODERATING - Nugroho Dwi Ananto; Indira Januarti (Diponegoro Journal of Accounting, 2016)
This research aims to analyze internal and external factors  that affect the behavior  of accounting student towards the intention of plagiarism act. Variables that are examined in this research are as follows: self awareness, personal attitude, self competence, internet facility, and control of academic institutions. Control of academic institutions was used as independent variable and c was used as dependent variable while pressure was used as moderating variable. Data used in this research was primary data that was collected through questionnaire. Samples were selected by using purposive random sampling method. Respondents in this research were accounting students of Diponegoro University. The respondents consist of those who were in S1, S2, and S3. 100 respondents were selected for this research. The data collected were analyzed by using regression analysis and moderation regression analysis. The result showed that personal attitude didn’t have significant influence toward the behavior of plagiarism act while self awareness, self competence, dan internet facility had significant ifluence toward the behavior of plagiarism act. Moreover, pressure was unable to moderate the influence of self competence to the behavior of plagiarism act.